Efektivitas Penerapan Presensi Berbasis Titik Lokasi Melalui Aplikasi Simak Dihati Dalam Meningkatkan Kedisiplinan Pegawai (Studi Kasus: Kantor Camat Denpasar Selatan) - Rahayu, Kadek Intan Siti Rahayu; Wijaya, Komang Adi Sastra; Purnamaningsih, Putu Eka (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
The implementation of the Simak Dihati attendance system is one of the applications applied by the South Denpasar Sub-district Office with the aim of improving employee discipline, especially in terms of punctuality. During its implementation at the South Denpasar Sub-district Office since 2022, the Simak Dihati attendance system has encountered several issues such as frequent application errors, rejections when employees take selfies and submit their location points, and uneven employee capabilities. The purpose of this research is to determine the effectiveness of the implementation of the Simak Dihati attendance system in improving employee discipline at the South Denpasar Sub-district Office. This research uses a qualitative method with data collection techniques including observation, interviews, and documentation. The research results based on effectiveness indicators according to Tangkilisan (2005), which consist of Target Achievement, Adaptation Ability, Job Satisfaction, and Responsibility, show that the implementation of online attendance (Simak Dihati) at the South Denpasar Sub-district Office has been effective in terms of target achievement, job satisfaction, and responsibility indicators. However, it has not fully met the Adaptation Ability indicator because many employees are still unable to use the Simak Dihati attendance system, especially older or senior employees, and the devices used often experience issues, thus hindering the implementation of the Simak Dihati attendance system.